99.8k views
3 votes
Can someone explain how to solve it?

Can someone explain how to solve it?-example-1
User Constexpr
by
4.7k points

2 Answers

2 votes
First replace the variables
10=3+x —> x=10-3=7
11= 4+x —> x=11-4=7
12=5+x —> x=12-5=7
13=6+x —> x=13-6=7
All of these equations equal 7
So c=h+7

User Mariusz Jamro
by
4.9k points
2 votes
C=h+7
Going down the list you check your work. So basically it’s asking what is the rule of this equation. In this case it’s c=h+7. So 3+7 4+7 5+7 6+7. 3,4,5,6 are all of the x values. When you add seven to each one you’ll find that it equals y. So 3(x) + 7= 10(y)
User Mike Edwards
by
5.5k points